An updated list of drugs suspected to be associated with immune thrombocytopenia based on the WHO pharmacovigilance database - Fuentes, Ségolène; Chrétien, Basile; Dolladille, Charles; Alexandre, Joachim; Dumont, Anaël; Nguyen, Alexandre; Boysson, Hubert; Chèze, Stéphane; Maigné, G.; Aouba, Achille; Deshayes, Samuel (Blood, 2022)
Letter to Blood| August 25, 2022 An updated list of drugs suspected to be associated with immune thrombocytopenia based on the WHO pharmacovigilance database Clinical Trials & Observations Ségolène Fuentes, Ségolène Fuentes Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Basile Chrétien, Basile Chrétien Department of Pharmacology, CHU de Caen Normandie, Caen, France; https://orcid.org/0000-0002-7483-2489 Search for other works by this author on: This Site PubMed Google Scholar Charles Dolladille, Charles Dolladille Department of Pharmacology, CHU de Caen Normandie, Caen, France;Normandie University, UNICAEN, INSERM U1086 ANTICIPE, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Joachim Alexandre, Joachim Alexandre Department of Pharmacology, CHU de Caen Normandie, Caen, France;Normandie University, UNICAEN, INSERM U1086 ANTICIPE, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Anaël Dumont, Anaël Dumont Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Alexandre Nguyen, Alexandre Nguyen Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Hubert de Boysson, Hubert de Boysson Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France;Normandie University, UNICAEN, UR4650 PSIR, CHU de Caen Normandie, Caen, France; and Search for other works by this author on: This Site PubMed Google Scholar Stéphane Chèze, Stéphane Chèze Department of Hematology, CHU de Caen Normandie, Caen, France Search for other works by this author on: This Site PubMed Google Scholar Gwénola Maigné, Gwénola Maigné Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France; Search for other works by this author on: This Site PubMed Google Scholar Achille Aouba, Achille Aouba Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France;Normandie University, UNICAEN, UR4650 PSIR, CHU de Caen Normandie, Caen, France; and Search for other works by this author on: This Site PubMed Google Scholar Samuel Deshayes Samuel Deshayes Department of Internal Medicine, Normandie University, Université de Caen Normandie (UNICAEN), Centre Hospitalo-Universitaire (CHU) de Caen Normandie, Caen, France;Normandie University, UNICAEN, UR4650 PSIR, CHU de Caen Normandie, Caen, France; and https://orcid.org/0000-0001-8887-3233 Search for other works by this author on: This Site PubMed Google Scholar Blood (2022) 140 (8): 922–927. https://doi.org/10.1182/blood.2022015936 Article history Submitted: February 14, 2022 Accepted: June 29, 2022 First Edition: July 8, 2022 Share Icon Share Facebook Twitter LinkedIn MailTo Tools Icon Tools Request Permissions Cite Icon Cite Search Site Citation Ségolène Fuentes, Basile Chrétien, Charles Dolladille, Joachim Alexandre, Anaël Dumont, Alexandre Nguyen, Hubert de Boysson, Stéphane Chèze, Gwénola Maigné, Achille Aouba, Samuel Deshayes; An updated list of drugs suspected to be associated with immune thrombocytopenia based on the WHO pharmacovigilance database. Blood 2022; 140 (8): 922–927. doi: https://doi.org/10.1182/blood.2022015936 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsBlood Search Subjects: Clinical Trials and Observations, Platelets and Thrombopoiesis, Thrombocytopenia TO THE EDITOR: Iatrogenic thrombocytopenia is a common adverse drug reaction (ADR) that can be caused by various mechanisms, including drug-associated immune thrombocytopenia (DITP), whose prognosis is generally favorable when the suspected drug is withdrawn.1-4 However, the diagnosis of DITP remains challenging for several reasons. First, there is limited evidence about this rare disease because of a lack of recent powerful studies.2-6 Second, the involved patients frequently have comorbidities and are thereby often exposed to several drugs, which may be possible causes of secondary immune thrombocytopenia (ITP) leading to frequent misdiagnoses.2,7,8 Moreover, the withdrawal of some drugs can be highly challenging a…